Analysis of early neonatal case fatality rate among newborns with congenital hydrocephalus, a 2000–2014 multi‐country registry‐based study. Issue 12 (28th May 2022) - Gili, Juan Antonio; López‐Camelo, Jorge Santiago; Nembhard, Wendy N.; Bakker, Marian; de Walle, Hermien E. K.; Stallings, Erin B.; Kancherla, Vijaya; Contiero, Paolo; Dastgiri, Saeed; Feldkamp, Marcia L.; Nance, Amy; et al.
Abstract: Background: Congenital hydrocephalus (CH) comprises a heterogeneous group of birth anomalies with a wide‐ranging prevalence across geographic regions and registry type. The aim of the present study was to analyze the early neonatal case fatality rate (CFR) and total birth prevalence of newborns diagnosed with CH. Methods: Data were provided by 25 registries from four continents participating in the International Clearinghouse for Birth Defects Surveillance and Research (ICBDSR) on births ascertained between 2000 and 2014. Two CH rates were calculated using a Poisson distribution: early neonatal CFR (death within 7 days) per 100 liveborn CH cases (CFR) and total birth prevalence rate (BPR) per 10, 000 births (including live births and stillbirths) (BPR). Heterogeneity between registries was calculated using a meta‐analysis approach with random effects. Temporal trends in CFR and BPR within registries were evaluated through Poisson regression modeling. Results: A total of 13, 112 CH cases among 19, 293, 280 total births were analyzed. The early neonatal CFR was 5.9 per 100 liveborn cases, 95% confidence interval (CI): 5.4–6.8. The CFR among syndromic cases was 2.7 times (95% CI: 2.2–3.3) higher than among non‐syndromic cases (10.4% [95% CI: 9.3–11.7] and 4.4% [95% CI: 3.7–5.2], respectively). The total BPR was 6.8 per 10, 000 births (95% CI: 6.7–6.9). Stratified by elective termination of pregnancy for fetal anomalies (ETOPFA), region and system, higher CFR were observed alongside higher BPR rates. The early neonatal CFR and total BPR did not show temporal variation, with the exception of a CFR decrease in one registry. Conclusions: Findings of early neonatal CFR and total BPR were highly heterogeneous among registries participating in ICBDSR. Most registries with higher CFR also had higher BPR. Differences were attributable to type of registry (hospital‐based vs. population‐based), ETOPFA (allowed yes or no) and geographical regions. These findings contribute to the understanding of regional differences of CH occurrence and early neonatal deaths.